Socialization of Application Digital Media for Hybrid Learning - Tarigan, Fatin Nadifa; Nasution, Alwi Fahruzy; Hidayati, Taufika; Priono, Joko; Siregar, Epi Supriyani (Journal of Community Research and Service, 2022)
The unstable condition of Covid-19 pandemic caused teachers be innovative in combining both online learning and face to face learning. Nevertheless, the application of digital media during hybrid learning is still a big issue for teachers in SD Adhyaksa, Medan City, North Sumatra Province. In consequence, it is necessary to hold community service by means of socialization of application digital media for hybrid learning. This service aims to socialize and offer training related to the use of online study through Google Classroom and Google Form to teachers and employees at Elementary School. The methods used to carry out this service activity were lecturing method and direct practice. It started from providing material introduction and direct practice of using Google Classroom and Google Form for teachers. With a variety of features it has, Google Classroom can be used to demonstrate or visualize concept of lessons with no face to face needed. From this service activity the teachers who tried Google Classroom and Google Form got good results. They understood how to apply digital media either in online learning or in offline learning. After getting materials and practices for applying digital media, Google Classroom and Google Form, teachers are accustomed to use these online media for hybrid learning.